"At a Certain Age It's Not Appropriate to Monitor One's Child": Perceptions of Parental Mediation of Emerging Adult Interactive Technology Use. (October 2015) - Vaterlaus, J. Mitchell; Beckert, Troy E.; Bird, Clare V.
Little is known about the role parental mediation plays in emerging adult technology use. As such, the current exploratory study was designed to identify the prevalence of parental mediation during this developmental period, ascertain how parents mediate, and understand the reasons parents elect not to mediate. Eighty-two unmarried college participants and 76 of their parents participated in this descriptive qualitative study. A majority of emerging adults and parents reported that parents did not mediate their child's interactive technology. Reasons for not monitoring revolved around parental trust, child maturity, and parental priorities. For those who reported parental mediation, monitoring content and usage was the mediation technique most frequently implemented.